Regional differences in infection control conditions in a sample of primary health care services in Brazil - Mauro Henrique Nogueira Guimarães de Abreu; Vera Lúcia Silva Resende; Kyu Ha Lee; Antônio Thomaz Gonzaga da Matta-Machado; Jacqueline Rose Starr (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
International guidelines have pointed out the importance of the physical environment of health care facilities in preventing and controlling infection. We aimed to describe the physical environment of dental care facilities in Brazil in 2014, focusing on characteristics designed to control infections. Exactly 16,202 dental offices in the Brazilian Unified National Health System (SUS) participated in this survey. Trained researchers extracted information about the infection control characteristics of health facilities by using a structured instrument. We used data from 12 dichotomous questions that evaluated the wall, floor, sink and tap conditions, and the presence and condition of sterilization equipment. We calculated a score by summing the number of characteristics handled appropriately for infection control, which could range from 0 to 12. Hierarchical cluster analyses were developed. None of the 12 criteria were met by all the oral health teams. Only 208 (1.3%) dental offices correctly performed all 12-infection control practices. Two clusters, with different frequencies of structure for infection control in dental offices, were identified. South and Southeast regions had the highest frequencies for Cluster 1, with better structure of infection control in dental offices. Dental care facilities of oral health teams were not typically meeting the infection control guidelines regarding clinic design and equipment. Adherence to the guidelines varied among the Brazilian geographic regions.